ТЕҢСИЗЛИКЛЕРДИ ФУНКЦИЯНЫҢ ҚӘСИЙЕТЛЕРИНЕН ПАЙДАЛАНЫП ДӘЛИЙЛЛЕЎ ЖОЛЛАРЫ - Қошкарбаева, Р.; Касымов, М.; Өмирбаева, К. (FAN va JAMIYAT, 2016)
The article deals with the issues of ways of presentation and explanation of inequality with the help of functions of inequalities. At the academic lyceums and professional colleges it is recommended to teach this material at the optional courses and in the clubs.